2022
DOI: 10.1371/journal.pone.0262423
|View full text |Cite
|
Sign up to set email alerts
|

High-altitude is associated with better short-term survival in critically ill COVID-19 patients admitted to the ICU

Abstract: Background Multiple studies have attempted to elucidate the relationship between chronic hypoxia and SARS-CoV-2 infection. It seems that high-altitude is associated with lower COVID-19 related mortality and incidence rates; nevertheless, all the data came from observational studies, being this the first one looking into prospectively collected clinical data from severely ill patients residing at two significantly different altitudes. Methods A prospective cohort, a two-center study among COVID-19 confirmed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 72 publications
3
20
0
Order By: Relevance
“…The study was carried out in Ecuador, one of the smallest Latin American countries, located in the equatorial line and bordering the Pacific Ocean. Ecuador shares borders with Peru and Colombia, and its current population is estimated to be 17,577,116 inhabitants [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was carried out in Ecuador, one of the smallest Latin American countries, located in the equatorial line and bordering the Pacific Ocean. Ecuador shares borders with Peru and Colombia, and its current population is estimated to be 17,577,116 inhabitants [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, within the study of the physiopathology of Long-COVID, the role of hypobaric hypoxia to which high-altitude residents are exposed has not been addressed [ 22 , 23 ]. In this regard, it has been speculated that living at high altitudes is associated with lower mortality due to COVID-19 [ 24 ]. We believe that the phenotypic and adaptive differences that populations with a high degree of mestizos possess may cause differences in the characteristics that Long-COVID has been shown to have in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…All the available studies showed that the more severe the infection was, the greatest the lung capacity alteration [19]. Although earlier mechanical ventilation has been associated with better survival among severely ill COVID-19 patients, it also behaves as a predictor of radiological and spirometric abnormalities [21,23,24].…”
Section: Pulmonary Sequelaementioning
confidence: 99%
“…population density, overcrowding activities or migration) and lastly, (3) the direct or indirect consequences of the environment on virulence or viral transmission (i.e. ozone, UV exposure or cold) 8 , 9 , 12 , 13 , 17 , 20 .…”
Section: Introductionmentioning
confidence: 99%